Governing the Formation of Board of Directors in Saudi Joint Stock Companies - Alhejaili, Mohammad Omar (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to explore the governance issues related to the formation of the board of directors of joint stock companies by investigating the legal code of board of director’s formation within the Saudi company law using an analytical and comparative approach. The study will highlight the areas of strengths and weaknesses of the company legal system in this regard as well as provide recommendations to counteract the weaknesses, hence improving the methods, The governance of forming the board of directors is in the interest of the company, society and the economic system in general, and the Saudi system deals with the method of formation and the number of members in light of a number of data that affect the extent of governance of the formation of the board of directors of joint-stock companies.